EZH2–miR‐30d–KPNB1 pathway regulates malignant peripheral nerve sheath tumour cell survival and tumourigenesis. Issue 3 (February 2014) - Zhang, Pingyu; Garnett, Jeannine; Creighton, Chad J; Al Sannaa, Ghadah Abbas; Igram, Davis R; Lazar, Alexander; Liu, Xiuping; Liu, Changgong; Pollock, Raphael E
Abstract Malignant peripheral nerve sheath tumours (MPNSTs), which develop sporadically or from neurofibromatosis, recur frequently with high metastatic potential and poor outcome. The polycomb group protein enhancer of zeste homologue 2 (EZH2) is an important regulator for various human malignancies. However, the function of EZH2 in MPNSTs is unknown. Here we report that the EZH2–miR‐30d–KPNB1 signalling pathway is critical for MPNST tumour cell survival in vitro and tumourigenicity in vivo. Up‐regulated EZH2 in MPNST inhibits miR‐30d transcription via promoter binding activity, leading to enhanced expression of the nuclear transport receptor KPNB1 that is inhibited by miR‐30d targeting of KPNB1 3′ UTR region. Furthermore, inhibition of EZH2 or KPNB1, or miR‐30d over‐expression, induces MPNST cell apoptosis in vitro and suppresses tumourigenesis in vivo. More importantly, forced over‐expression of KPNB1 rescues MPNST cell apoptosis induced by EZH2 knockdown. Immunohistochemical analyses show that EZH2 and KPNB1 over‐expression is observed in human MPNST specimens and is negatively associated with miR‐30d expression. Our findings identify a novel signalling pathway involved in MPNST tumourigenesis, and also suggest that EZH2–miR‐30d–KPNB1 signalling represents multiple potential therapeutic targetable nodes for MPNST. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.